Study of a High-Yield Cellulase System Created by Heavy-Ion Irradiation-Induced Mutagenesis of Aspergillus niger and Mixed Fermentation with Trichoderma reesei - Wang, Shu-Yang (Public Library of Science, 2015)

(untitled) (PLoS One)
The aim of this study was to evaluate and validate the efficiency of (12)C(6+) irradiation of Aspergillus niger (A. niger) or mutagenesis via mixed Trichoderma viride (T. viride) culturing as well as a liquid cultivation method for cellulase production via mixed Trichoderma reesei (T. reesei) and A. niger culture fermentation. The first mutagenesis approach was employed to optimize yield from a cellulase-producing strain via heavy-ion mutagenesis and high-throughput screening, and the second was to effectively achieve enzymatic hydrolysis of cellulase from a mixed culture of mutant T. viride and A. niger. We found that (12)C(6+)-ion irradiation induced changes in cellulase biosynthesis in A. niger but had no effect on the time course of the synthesis. It is notable that the exoglucanases (CBH) activities of A. niger strains H11-1 and H differed (6.71 U/mL vs. 6.01 U/mL) and were significantly higher than that of A. niger mutant H3-1. Compared with strain H, the filter paper assay (FPA), endoglucanase (EG) and β-glucosidase (BGL) activities of mutant strain H11-1 were increased by 250.26%, 30.26% and 34.91%, respectively. A mixed culture system was successfully optimized, and the best ratio of T. reesei to A. niger was 5:1 for 96 h with simultaneous inoculation. The BGL activity of the mixed culture increased after 72 h. At 96 h, the FPA and BGL activities of the mixed culture were 689.00 and 797.15 U/mL, respectively, significantly higher than those of monocultures, which were 408.70 and 646.98 U/mL for T. reesei and 447.29 and 658.89 U/mL for A. niger, respectively. The EG activity of the mixed culture was 2342.81 U/mL, a value that was significantly higher than that of monocultures at 2206.57 U/mL for T. reesei and 1727.62 U/mL for A. niger. In summary, cellulose production and hydrolysis yields were significantly enhanced by the proposed combination scheme.